KEBERADAAN FASILITAS TAMAN HIJAU KOTA PURWODADI DAN PENGARUHNYA TERHADAP KENYAMANAN PENGUNJUNG - Suharyani, Suharyani; Wibowo, Febri Arsetyo (Sinektika: Jurnal Arsitektur, 2018)
Open spaces located in urban areas have functioned as spaces for citizen interaction for a variety of useful functions and interests. The existence of existing city parks can be utilized by citizens of the city to the fullest. This has become one of the alternatives that can be utilized by the city community for more comfortable interactions. Judging from the function of researchers interested in conducting research by formulating the problem namely how the completeness of facilities and comfort in Green Garden Purwodadi City and how comfort is felt when using the facilities available. Green Open Space Arrangement (RTH) is still being promoted by the regency government due to the lack of open green space in Grobogan Regency. So far there have only been 12.8% of public green open space, while at least it requires 20% of green open space from urban areas. Therefore, Purwodadi Green Park was chosen as the object of research. Purwodadi Green Park is a new vehicle for free and fun family recreation in downtown Purwodadi, Grobogan Regency. This study aims to find out how the criteria of a comfortable city park to interact for urban communities. Then to find out the level of comfort, can be known by using data collection methods of observation and open questionnaires. The result of study is that Purwodadi Green Park not in accordance with established standards. The incomplete facilities have resulted in visitors inconvenience caused by the lack of trees in the green park, so that during the day visitors feel the heat due to direct exposure to sunlight.